Cathodic Stripping Voltammetric Determination of Febuxostat in Pharmaceutical Dosage Form and Plasma Samples - Habib,I. H. I. (2016)
Febuxostat FEB was determined by differential pulse ''DP'' adsorptive stripping voltammetry and hanging mercury drop electrode. In 0.04 mol L-1 Britton-Robinson buffer solution, pH 10, an irreversible electrochemical reaction took place at about -350 mV, and the peak current was linearly varied over the concentration range of 12.5-200 ng mL-1 FEB, with correlation coefficients of 0.9995, after 60 s accumulation time, stirring at a speed of 600 rpm, rest for 10 s, then cathodic stripping sweep from -100 to 600 mV, with a scan rate of 60 mV/s. The limits of detection and quantization were 6.93, 23.09 ng mL-1. The method was applicable for determining FEB in pharmaceutical tablets and in spiked plasma. The results of the proposed method were compared with that obtained by the UV-spectrophotometric technique.